P8 An ex-vivo model of 18F-sodium fluoride MICRO-PET-CTCA in cadaveric hearts. (26th October 2016) - Moss, AJ; Adamson, PD; Tavares, A; Dweck, MR; Newby, DE
Abstract : Microcalcification is a key pathological feature of vulnerable atherosclerotic plaques. 18F-Sodium fluoride (18F-NaF) is a highly sensitive radiotracer that preferentially binds to microcalcification in the carotid vasculature. In the coronary arteries, 18F-NaF identifies high-risk and culprit plaques following myocardial infarction and improves cardiovascular risk stratification. However there is a need to better understand its mechanism of binding in coronary atheroma, ideally using histology as a gold standard comparator. In this study, we sought to develop a model that might provide this validation, establishing a method for scanning cadaveric hearts ex-vivo using 18F-NaF microPET-CTCA. Selective catheterisation of the coronary ostia was established in ten cadaveric porcine hearts. 18F-NaF and CT contrast were then administered down the coronary arteries and the optimal dosing and time course of injection for both agents investigated. Contrast opacification of vessel lumens using varying dilutions of a contrast-starch mixture were investigated for CT imaging. Different concentrations (MBq/mL) of 18F-NaF were administered and the PET signal assessed over varying bed-times using micro-PET/CT. Phantom and ex-vivo studies on intact porcine hearts demonstrated that the optimal contrast-starch mixture was 2% Omnipaque and 3% methyl cellulose. 18F-NaF infusion with 100kBq/mL, over 20 minutes at an infusion rate of 1.0 mL/min provided excellent signal-to-noise images of coronary artery microcalcification. Longer incubation times did not increase measured 18F-NaF activity. Using this protocol, we obtained high-resolution PET/CT images of the coronary arteries, indicating that it holds major potential in the validation of this imaging technique and the study of sudden cardiac death.